Photocatalytic performance of acid exfoliated graphitic carbon nitride (g-C3N4) for the degradation of dye under direct sunlight - Solayman, H. M.; Noor Yahida, Yahya; Leong, Kah Hon; Hossain, Md. Kamal; Kang, Kang; Sim, Lan Ching; Zoh, Kyung-Duk; Khan, Md. Badiuzzaman; Azrina, Abd Aziz (Elsevier B.V., 2024)
Graphitic carbon nitride (g-C3N4) is one of the most promising semiconductor materials applied in photocatalytic applications. However, the photocatalytic performance of bulk g-C3N4 was not satisfactory due to poor visible-light absorption, quick recombination, and low amount of active interfacial reaction sites. In this study, we have modified the bulk g-C3N4 by acid (nitric, hydrochloric and sulphuric) exfoliation to enhance the photocatalytic degradation of methylene blue (MB) and methyl orange (MO) dye. Sulfuric acid-treated g-C3N4 photocatalyst (CN-S) presented significant photocatalytic degradation toward both MO and MB compared to the pristine g-C3N4. The photocatalytic degradation performance for CN-S is found to be ∼ 96.89 % for MO and ∼ 93.12 % for MB under 150 min under direct sunlight irradiation. Free radical scavenging tests showed the superoxide radicals (•O2−) were mostly responsible to the photodegradation of dyes while comparing to hydroxyl radicals (•OH) and photo-induced holes (h+). Which is attributed by Photoluminescence (PL) and time resolved PL emission spectra indicated a low electron-hole pair’s (e−/h+) recombination and longer charge-carrier lifetime. Moreover, the CN-S showed excellent recyclability for up to 5 runs with a slight reduction of degradation performance from 96.89 to 90.55 % for MO and 93.12 % to 88.84 % for MB dye, respectively. Ultimately, the results demonstrated that CN-S was a superb photocatalyst for the elimination and deterioration of MB and MO dyes from wastewater.